Application of OMAX at UD. Meatball Biawu for Analyze Measurement Productivity Work - Dewirna Tantu; Fidya Ayustina Yacub; Difa N.A Nadjamuddin; Eduart Wolok; Nurfaisal Harun (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2024)
UD. Meatball Biawu is a company operating in the manufacturing sector whose main work is operational production of finished food ingredients in the form of meatballs. The absence of systematic measurement of company productivity and labor productivity means the company is unable to meet production targets or maximize production capacity. Therefore UD. Meatball Biawu seeks to increase its productivity by measuring each productivity criterion. The method used to carry out measurements is the Objective Matrix (OMAX) method. Based on research results, the best productivity occurred in March 2023, amounting to 727.86 due to high production output which exceeded production capacity, requiring additional labor. And the worst productivity level occurred in November 2022 amounting to 651.86 due to the many production defects so repairs had to be made by re-manufacturing.